1992
DOI: 10.1149/1.2069231
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐Film Cadmium Mercury Telluride Prepared by Nonaqueous Electrodeposition

Abstract: Using a new electrodeposition process, thin-film cadmium mercury telluride, Cd=Hg~_=Te, with (1 -x) no greater than 0.4, was electrodeposited onto an indium tin oxide-coated glass cathode. The deposition bath contained Cd(II), Hg(II), and tri-n-butyl phosphine telluride in propylene carbonate, and its composition was shown to have a direct effect on the composition of the electrodeposited films. Film composition was determined by atomic absorption spectroscopy and by proton-induced x-ray emission. Structural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…MCT has also been deposited onto ITO-coated glass [146]. A bath is maintained at 95 C in a three-compartment cell with a Cd metal counter electrode and a Ag/AgCl reference electrode.…”
Section: Mercury Cadmium Telluride (Hg 1àx CD X Te)mentioning
confidence: 99%
“…MCT has also been deposited onto ITO-coated glass [146]. A bath is maintained at 95 C in a three-compartment cell with a Cd metal counter electrode and a Ag/AgCl reference electrode.…”
Section: Mercury Cadmium Telluride (Hg 1àx CD X Te)mentioning
confidence: 99%
“…The EPMA results for the two previous deposits were encouraging, as it showed that the compositions of the alloy could be varied just by changing the EC-ALE program. But, in order to find out if there was a real control over the deposit composition, a series of experiments were performed by varying the HgTe cycles in the period while keeping the same number of CdTe cycles(5) and the number of periods (20). The resulting deposits were analyzed by EPMA to determine their compositions.…”
Section: Resultsmentioning
confidence: 99%
“…Electrodeposition is a simple and less expensive method and can be used to prepare high quality MCT films. Some work has been done in the field of deposition of MCT by co-deposition [3,[15][16][17][18][19] and electrodeposition in non aqueous solutions [20,21]. There has been moderate success with these techniques as the deposited MCT is not always crystalline.…”
Section: Introductionmentioning
confidence: 99%
“…Although a variety of methods have been used for the preparation of CMT films, electrodeposition renders itself as an attractive option due to its simplicity, low cost and potential for large-scale production. Electrodeposition from aqueous [2][3][4][5][6][7] and from non-aqueous solutions [8] and voltammetric study of electrodeposition have been reported [9]. From these reports it appears that electrodeposition yields uniform and adherent films only for compositions (0.82 < x < 1) that correspond to bandgap energies in the range 1.1-1.5 eV.…”
Section: Introductionmentioning
confidence: 99%